Different routes - one goal: how companies recruit apprentices - Ebbinghaus, Margit [Verfasser] (My University, 2011)
"'Trainees - a scarce commodity' was the headline in Technology Review in December 2009. Increasingly often this kind of report appears in the press, drawing attention to the impacts of demographic change, falling numbers of school-leavers, fewer applicants for training places and the resulting unfilled apprenticeship vacancies. Since this demographic downturn is set to continue for the time being, the question that arises is, what are companies doing in order to get hold of this 'scarce commodity'? The article focuses on the beginning of the process of filling an apprenticeship vacancy - i. e. recruiting potential applicants – and the strategies adopted by companies." (Autorenreferat, BIBB-Doku)
Keywords: S 5.3 Personalentwicklung; P 2.3 Auszubildende; G 1.3.1.1 Ausbildungsstellenmarkt; S 3.2 Unternehmen und Behörden; Betrieb; Personalgewinnung; Ausbildungsstellenbewerber; Ausbildungsmarketing; Betriebsbefragung